RANCANG BANGUN ROMPI WEARABLE UNTUK DETEKSI DAN KOREKSI POSTUR DUDUK SISWA SECARA REAL-TIME BERBASIS ESP32 DAN SENSOR MPU6050 DI MI AL-KHOERIYYAH - M. Faqih Badruzaman; Ardelia Astriany Rizky (INFOKOM (Informatika & Komputer), 2026)
This study aims to design and evaluate a wearable vest device capable of detecting and providing real-time alerts when elementary school students begin to slouch while sitting. The system employs an MPU6050 sensor attached to the back to measure body tilt angles, with data sent to an ESP32 microcontroller for processing. When the tilt angle exceeds a certain threshold, a buzzer is activated as a warning. Posture information is also transmitted to an ESP8266 using the ESP-NOW protocol and displayed on an LCD without requiring an internet connection. The device was tested directly in a classroom setting at MI Al-Khoeriyyah and demonstrated the ability to provide real-time responses, improve students’ awareness of proper sitting posture, and remain comfortable for use during extended learning activities.